Promoción de los atractivos turísticos y su contribución a la economía en el cantón Buena Fe, Provincia de Los Ríos, año 2021 - Carmigniani Pluas, Karelis Milena (2021)
The research is based in the Buena Fe canton, Los Ríos province, located north of the province, central Ecuador, due to its location, it is close to the Ecuadorian highlands region, it has a tropical climate, which allows have a fertile, productive land, recognized for its prosperous soil throughout the country, in addition to having a diverse fauna and flora due to its particular hydrography. At present, the Buena Fe canton has a number of natural and artificial attractions, extensive rivers, waterfalls, cattle ranches, parks, restaurants, hotels, inns and complexes, which make the city a corner to spend pleasant moments in families and friends, out of stress and routine life. By promoting the tourism sector of the Buena Fe canton, the economy of the sector will be growing, because jobs are generated, sales increase from the informal stall on the outskirts of tourist places to the personnel who work in the chain of tourism.